THE EFFECTS OF COORDINATION ON PUBLIC SERVICE QUALITY AT THE OFFICE OF ARCHIVES AND LIBRARY OF SUMEDANG REGENCY - Hermayanty, Irma (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2021)
This study aims to determine the effects of Coordination on the Public Service Quality at the Office of Archives and Library of Sumedang Regency and to determine the relationship between Coordination and Public Services Quality at the Office of Archives and Library of Sumedang Regency. The method used in this study is a quantitative research method to test the predetermined hypothesis. In this study, researchers used inferential descriptive data analysis techniques to describe the collected data as it is by making general conclusions. The sampling technique used in this study is a saturated sampling technique with a population of 70 people to obtain a sample size of 70 respondents.Based on the results of the study, it can be illustrated that the coordination at the Office of Archives and Library of Sumedang Regency is sufficient, reaching 67.80%, and the Public Service Quality at the Office of Archives and Library of Sumedang Regency reaches 65.70%, and this figure is categorized as sufficient. The correlation between coordination and public service quality at the Office of Archives and Library of Sumedang Regency with a correlation coefficient of 0.52 is in the medium category. Meanwhile, the effect of coordination public service quality at the Office of Archives and Library of Sumedang Regency reached 27%, while the remaining 73% was affected by unexamined factors called the epsilon factor.